Association between being overweight and oral health in Serbian schoolchildren. Issue 6 (15th December 2014) - Markovic, Dejan; Ristic‐Medic, Danijela; Vucic, Vesna; Mitrovic, Goran; Nikolic Ivosevic, Jelena; Peric, Tamara; Karadzic, Ivana
<x xml:space="preserve">Abstract</x> Background Childhood obesity, dental caries, and periodontal disease are major public health problems due to their adverse impact on the growth and development of children. Aim To examine the association between nutritional status, oral health, and lifestyle habits among schoolchildren in Serbia. Design This cross‐sectional study assessed 422 children and adolescents aged 6–18 years with the following dental indexes analyzed: DMF/dmf (decayed, missed, and filled teeth), plaque index (PI), and gingival index (GI). Depending on their nutritional status, the subjects were categorized, as being 'normal weight, ' 'at risk of overweight, ' and 'overweight.' Logistic regression was applied to study the association between the dental indexes and independent variables: gender, age, toothbrushing, nutritional status, and lifestyle factors. Results Being overweight positively correlated with GI, but negatively correlated with the DMF/dmf index among the participants. Multivariate analysis showed a strong association between the weight category and toothbrushing with GI and PI. Overweight children (6–11 years) were less likely to have caries, whereas in older children/adolescents (12–18 years), caries was associated with the intake of sugar‐sweetened juices. Conclusions Being overweight was found to be significantly associated with a higher probability of developing gingivitis and negatively associated with caries prevalence in Serbian children and adolescents.